(-8z-3z+5)+(-3z+9z+2)=

Simple and best practice solution for (-8z-3z+5)+(-3z+9z+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8z-3z+5)+(-3z+9z+2)= equation:


Simplifying
(-8z + -3z + 5) + (-3z + 9z + 2) = 0

Reorder the terms:
(5 + -8z + -3z) + (-3z + 9z + 2) = 0

Combine like terms: -8z + -3z = -11z
(5 + -11z) + (-3z + 9z + 2) = 0

Remove parenthesis around (5 + -11z)
5 + -11z + (-3z + 9z + 2) = 0

Reorder the terms:
5 + -11z + (2 + -3z + 9z) = 0

Combine like terms: -3z + 9z = 6z
5 + -11z + (2 + 6z) = 0

Remove parenthesis around (2 + 6z)
5 + -11z + 2 + 6z = 0

Reorder the terms:
5 + 2 + -11z + 6z = 0

Combine like terms: 5 + 2 = 7
7 + -11z + 6z = 0

Combine like terms: -11z + 6z = -5z
7 + -5z = 0

Solving
7 + -5z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -5z = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -5z = 0 + -7
-5z = 0 + -7

Combine like terms: 0 + -7 = -7
-5z = -7

Divide each side by '-5'.
z = 1.4

Simplifying
z = 1.4

See similar equations:

| m=-1-(-3) | | 13-2(3x+8)=7x-(x+11) | | 3(2x)(2x)= | | 14+3x=35 | | -4(5-3x)=76 | | y^2-16y+55= | | 5(-2/3)=-10/3 | | 39=12+3x | | 25c^2+70c+49=0 | | (5+a)(5a+3)=0 | | -2(2x+4)=-24 | | -5(x-y)=114 | | 2x=15-2 | | -9(-4)=36 | | -5x+y=114 | | 8+7x=6x+5 | | 17+7x=15+8x | | -5(x+y)=114 | | x^2-20x-3= | | -5x-y=114 | | (5+z)(5z+3)=0 | | 5u^2-39u-8=0 | | 934+1x=3x | | 2x+3/3-7x/6=2x/9+2 | | 2x^2+x+3= | | 40x+7.50=1250 | | 2x+3/3=2y-4 | | -1-4x=6x+9 | | 20-1/5d=3/10d+16 | | 32+72x=71x+36 | | x/5=y/4-2 | | -5x+3=5x-67 |

Equations solver categories